Exploring Moroccan Teachers’ Perspectives on Integrating ChatGPT into Higher Education Curriculum - Chahboune, Fatima; Zyad, Hicham (International Journal of Language and Literary Studies, 2025)
This study explores Moroccan teachers’ perspectives on ChatGPT-Assisted Language Teaching in higher education. It examines the various factors and barriers influencing the integration of ChatGPT into teaching practices. This study is framed within Technology Acceptance Model (Davis,1989). TAM encompasses the constructs that this study aims at exploring: Perceived usefulness (PU), perceived ease of use (PEU), perceived risk (PR), attitude and actual use (ChatGPT practices). An online questionnaire was administered to 50 professors in different Moroccan universities. Descriptive statistics show that most professors hold favorable perceptions of integrating ChatGPT in teaching practices. Notably, key barriers to ChatGPT adoption include ethical concerns, lack of training, and insufficient AI knowledge. Correlational analysis shows that PU and PEU significantly influence the actual use of ChatGPT. In contrast, there is no significant correlation between perceived risk and use. This study suggests that offering AI-training programs could enhance the integration of ChatGPT in Moroccan academia.